YOUKAI DALAM KOMIK INUYASHA KARYA TAKAHASHI RUMIKO - Sarin Saraswati, Putu (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Youkai often described as magical creature with supernatural power and strange performance. Most of Japanese believe that youkai are sign of bad omen, because of their strange appereance. But, Takahashi Rumiko, the author of Inuyasha, believe not all youkai are mean. She created some beautiful youkai with kind heart that can change the people opinion about youkai. The theory that used to analyzed youkai’s kind, roles, and meaning in Inuyasha’s comics are Marcel Danesi’s semiotic theory and Hiroko Yoda and Matt Alt’s youkai-logy’s concept. As the results, there are nine kind of youkai in Inuyasha’s comics, such as MukadeJourou, Shibugarasu, Sesshoumaru, Muonna, Shippou, Hachiemon, Urasue, Ninmenka, and Kirara. All of youkai in Inuyasha’s comics have same appereances and characteristics with the youkai in Japanese myth. There are three youkai with positive meaning, three negative meaning, and the other have contradictive meaning. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: youkai, Japanese myth, semiotic.